EMPOWERING THE SUSTAINABILITY OF THE MALAY LANGUAGE AS A COMMUNICATION TRANSMISSION AND ELEMENT OF IDENTITY - Irma Wani Othman; Mohd Khairi Lebai Ahmad; Mohd Sohaimi Esa, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The discussion in this paper refers to the effort to empower Malay language as a communication transmission bridge that is a significant element of Malaysian identity. The issues refined in this discussion refer to (i) The significance of the mother tongue as the language of knowledge in educational institutions, (ii) The balance between the use of Malay and English in HEIs, (iii) Efforts to uphold the Malay language as the national language, and (iv) The use national language in the public service sector. The application of a qualitative approach in this writing utilizes secondary sources such as research results in journals, scholarly writing, online news sources and public forums. The results of the study found that the government plays a critical role in the continued use and position of the Malay language by the people of this country and should be empowered by all parties. The rationale in the effort to dignify the Malay language is the maintenance of the nation state as enshrined in the national constitution which declares the Malay language as the official language of the country. The direction of this study is to pioneer the efforts of various parties in taking responsibility for preserving and empowering the mother tongue regardless of different backgrounds, religions and beliefs, in order to nourish the elements of identity, improve the quality and quality of the use of the national language, while maintaining the image of self-identity, race, and country. This is because in the face of global competition, the Malay language should be a bastion to defend the strength of the Malay nation's identity.